Comparison of morbidity and mortality between serologically positive and serologically negative dengue cases - Matti, Mahantesh; Maralihalli, Mahesh B.; Dinesh, Shilpa (International Journal of Contemporary Pediatrics, 2017)
Background: Dengue is most common arboviral disease caused by 4 types of dengue viruses. In most of the hospitals laboratory diagnosis is made by dengue serology using Rapid Immunochromatographic Test for NS1Ag, IgM and IgG antibodies. We found more morbidity and mortality in suspected dengue cases whose serology was negative for dengue. Methods: Children with clinical features suggestive for case definition for dengue, who belonged to group C of World Health organisation (WHO) guidelines for dengue fever (severe dengue), were included. They were categorised into dengue positive and dengue negative groups. The clinical features and complications of the disease between the two groups were compared. Results: 98 cases (77.8%) were serologically positive for dengue and 28 (22.2%) were negative. 39% of the patients with dengue negative serology developed hypotensive shock in comparison to 18% of dengue positive cases, mortality in serology negative cases (21%) was significantly higher than positive cases (8%). Conclusions: We could not find the reasons for more morbidity and mortality in seronegative dengue group, we stress up on improving the sensitivity and specificity of rapid diagnostic tests. More caution need to be taken for serology negative dengue cases. Epidemiological studies directed to find circulation of other viruses which causes dengue like symptoms should be made.